Investment in Non-Fungible Token (NFT) Digital Assets from Hadith Perspective: An Analysis of Gharar and Maisir Elements - Muhammad, Alfan Jawahir; Arif, Zainal; Nurafni, Fina (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2025)
The advancement of blockchain technology has introduced new digital economic instruments, notably Non-Fungible Tokens (NFTs), which function not only as representations of digital asset ownership but also as investment vehicles with highly volatile values. This development has sparked debates within Islamic law, particularly regarding the presence of gharar (excessive uncertainty) and maisir (speculative gambling) in NFT investment practices. This study examines the legal status of NFT investment from the perspective of ḥadīth-based muʿāmalah and analyzes the extent to which gharar and maisir are inherent in its transactional mechanisms. Employing a qualitative library research approach, this study uses descriptive-analytical methods to examine Prophetic ḥadīths prohibiting gharar and maisir, and contextualizes them within the technical characteristics and transaction structures of NFTs. Data sources include classical ḥadīth collections, ḥadīth commentaries, fiqh al-muʿāmalah literature, and relevant contemporary scholarly works. The findings indicate that NFTs, as digital assets, possess definable objects, ownership clarity, and verifiable delivery through blockchain technology, and therefore do not inherently constitute gharar. However, the use of cryptocurrency, extreme price volatility, and short-term speculative behavior may introduce elements of gharar and maisir if not accompanied by clear valuation, utility, and investment objectives. Consequently, the permissibility of NFT investment cannot be generalized but must be assessed contextually to uphold justice and the protection of wealth (ḥifẓ al-māl).